Heterogeneity of dormitory interpersonal conflict coping style and its negative emotional characteristics among college students: based on latent profile analysis - Pan, Junxing; Zhao, Xiaoyun; Lyu, Cui; Xu, Lili; Zhu, Ying (Frontiers in Psychology, 2025)
BackgroundDormitory interpersonal conflict coping style has an important impact on the quality of college students’ dormitory interpersonal relationships and emotional experiences. Still, previous studies have ignored the individual differences among college student groups, making it difficult to effectively classify these groups from the perspective of dormitory conflict coping style. This study aims to explore the potential categories of conflict coping styles in college students’ dormitories and their demographic characteristics, and to analyze the emotional differences among college students in different types of dormitory conflict coping groups, with the expectation of providing theoretical references for improving interpersonal relationships in college students’ dormitories.MethodsA convenience cluster sampling method was used to select 1,408 college students from a university in Anhui Province, China, to conduct an online survey. The Dormitory Interpersonal Relationship Questionnaire, the Dormitory Interpersonal Conflict Coping Style Questionnaire, and the Depression-Anxiety-Stress Scale Short Chinese Version were used for the investigation. First, we used “individual-centered” latent profile analysis to explore the categories of dormitory interpersonal conflict coping style; second, we used multifactorial binary logistic regression to explore the relationship between demographic variables and the potential categorization of dormitory interpersonal conflict coping style; and lastly, we used a difference-in-differences test to explore the emotional characteristics of different dormitory interpersonal conflict coping style groups.ResultsThe dormitory interpersonal conflict coping style group of Chinese college students was divided into two potential categories: the positive coping group (85.01%, 1,197 students) and the negative coping group (14.99%, 211 students). The results of binary logistic regression analysis showed that gender, grade, and type of specialty were all correlated with dormitory interpersonal conflict coping style in college: male students (OR = 1.86), senior students (OR sophomore = 1.44; OR juniors = 1.70), and non-literature and history majors (OR science and engineering = 1.57; OR arts and sports = 2.34) were more likely to choose negative responses to interpersonal conflicts in the dormitory (all p < 0.05). The positive coping group scored significantly lower on negative emotions than the negative coping group.ConclusionThere is significant group heterogeneity in the dormitory interpersonal conflict coping style of Chinese college students. Schools should guide college students to choose appropriate interpersonal conflict resolution strategies to create positive interpersonal relationships in dormitories.